PENERAPAN AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN BERBASIS ANDROID - Ratna Salkiawati; Ageng Ridho Ramadhan; Hendarman Lubis (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
AbstractThis research is aimed at the people of Bekasi city who have the criteria of studying information and communication techniques and aims to provide varied learning media, not boring, and increase learning motivation. The method used is the agile development method because development requires a short period of time. For students who learn to use books get a percentage increase in the value of 5.10%, while for students who learn to use augmented reality get a percentage increase in the value of 13.50% this means a higher increase in learning using augmented reality learning media than students who learn to use book. The conclusion of this study is that students can understand and master learning using augmented reality learning media and the existence of augmented reality learning media, learning becomes varied and the use of gadgets becomes more useful.Â Keywords : Augmented Reality; Agile Development Method; Learning Media; Kota Bekasi